1990
DOI: 10.1021/bi00473a021
|View full text |Cite
|
Sign up to set email alerts
|

The 56-59-kilodalton protein identified in untransformed steroid receptor complexes is a unique protein that exists in cytosol in a complex with both the 70- and 90-kilodalton heat shock proteins

Abstract: It has previously been shown that 9S, untransformed progestin, estrogen, androgen, and glucocorticoid receptor complexes in rabbit uterine and liver cytosols contain a 59-kDa protein [Tai, P. K., Maeda, Y., Nakao, K., Wakim, N. G., Duhring, J. L., & Faber, L. E. (1986) Biochemistry 25, 5269-5275]. In this work we show that the monoclonal antibody KN 382/EC1 raised against the rabbit 59-kDa protein reacts with 9S, untransformed glucocorticoid receptor complexes in cytosol prepared from human IM-9 lymphocytes bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
109
0
6

Year Published

1992
1992
1998
1998

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 210 publications
(116 citation statements)
references
References 43 publications
1
109
0
6
Order By: Relevance
“…On the basis of previous observations (Tai et al, 1986;Renoir et al, 1990;Sanchez et al, 1990). we have hypothesised that p59 is the human homologue of the 59-kDa rabbit protein associated with steroid receptors.…”
Section: Immunoblotting Studiesmentioning
confidence: 76%
See 4 more Smart Citations
“…On the basis of previous observations (Tai et al, 1986;Renoir et al, 1990;Sanchez et al, 1990). we have hypothesised that p59 is the human homologue of the 59-kDa rabbit protein associated with steroid receptors.…”
Section: Immunoblotting Studiesmentioning
confidence: 76%
“…3 indicate extensive structural similarity between glucocorticoid receptors from normal rat liver and transformed rat and human cell lines. It has been reported that only part of the molybdate-stabilized cytosolic glucocorticoid receptor from either rabbit liver (Tai et al, 1986), human IM-9 cells (Sanchez et al, 1990) or calf uterus (Renoir et al, 1990) reacted with the ECI monoclonal antibody against the 59-kDa component of the rabbit steroid receptors (Tai and Faber, 1985;Tai et al, 1986). Several lines of evidence therefore suggest that the 288-kDa complex is a distinct form of the untransformed cytosolic receptor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations